Efficient CO2 Reduction to Formate on CsPbI3 Nanocrystals Wrapped with Reduced Graphene Oxide - Hoang, Minh Tam; Han, Chen; Ma, Zhipeng; Mao, Xin; Yang, Yang; Madani, Sepideh Sadat; Shaw, Paul; Yang, Yongchao; Peng, Lingyi; Toe, Cui Ying; Pan, Jian; Amal, Rose; et al. (Nano-Micro Letters, 2023)
Transformation of greenhouse gas (CO2) into valuable chemicals and fuels is a promising route to address the global issues of climate change and the energy crisis. Metal halide perovskite catalysts have shown their potential in promoting CO2 reduction reaction (CO2RR), however, their low phase stability has limited their application perspective. Herein, we present a reduced graphene oxide (rGO) wrapped CsPbI3 perovskite nanocrystal (NC) CO2RR catalyst (CsPbI3/rGO), demonstrating enhanced stability in the aqueous electrolyte. The CsPbI3/rGO catalyst exhibited > 92% Faradaic efficiency toward formate production at a CO2RR current density of 12.7 mA cm−2. Comprehensive characterizations revealed the superior performance of the CsPbI3/rGO catalyst originated from the synergistic effects between the CsPbI3 NCs and rGO, i.e., rGO stabilized the α-CsPbI3 phase and tuned the charge distribution, thus lowered the energy barrier for the protonation process and the formation of *HCOO intermediate, which resulted in high CO2RR selectivity toward formate. This work shows a promising strategy to rationally design robust metal halide perovskites for achieving efficient CO2RR toward valuable fuels. Highlights: 1 A rational design of metal halide perovskites for achieving efficient CO2 reduction reaction was demonstrated. 2 The stability of CsPbI3 perovskite nanocrystal (NCs) in aqueous electrolyte was improved by compositing with reduced graphene oxide (rGO). 3 The CsPbI3/rGO catalyst exhibited > 92% Faradaic efficiency toward formate production with high current density which was associated with the synergistic effects between the CsPbI3 NCs and rGO.